2022
DOI: 10.30630/joiv.6.4.982
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Student Graduation using Naïve Bayes by Comparing between Random Oversampling and Feature Selections of Information Gain and Forward Selection

Abstract: Class-imbalanced data with high attribute dimensions in datasets frequently contribute to issues in a classification process as this can affect algorithms’ performance in the computing process because there are imbalanced numbers of data in each class and irrelevant attributes that must be processed; therefore, this needs for some techniques to overcome the class-imbalanced data and feature selection to reduce data complexity and irrelevant features. Therefore, this study applied random oversampling (ROs) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The Naive Bayes Classifier method is one of the algorithms in classification techniques that use probability and statistics presented by the English scientist Thomas Bayes, which predicts the likelihood of the future based on past experiences, thus known as Bayes' Theorem [5]. Some studies have shown the feasibility of this algorithm in building smart-system, such as the intelligent system for student personality classification [6], the system for NPC braking decisions in a racing game [7], and the new student admission recommendation system [8]. We choose the Naive Bayes algorithm for the machine learning method, using these studies as a reference in building smart security.…”
Section: Imentioning
confidence: 99%
“…The Naive Bayes Classifier method is one of the algorithms in classification techniques that use probability and statistics presented by the English scientist Thomas Bayes, which predicts the likelihood of the future based on past experiences, thus known as Bayes' Theorem [5]. Some studies have shown the feasibility of this algorithm in building smart-system, such as the intelligent system for student personality classification [6], the system for NPC braking decisions in a racing game [7], and the new student admission recommendation system [8]. We choose the Naive Bayes algorithm for the machine learning method, using these studies as a reference in building smart security.…”
Section: Imentioning
confidence: 99%
“…In work by [26] multiple linear regression (MLR), multilayer perceptron (MLP) and classification and regression tree (CART) are compared with MLP and CART performing better than MLR. Other than predicting the risk of dropout, there are studies on using machine learning to predict graduation [27], [28][29] has created a mobile application with deep learning to enhance English and Arabic vocabulary among children. The mobile application has recorded more than 90% accuracy for image classification.…”
Section: A Literature Reviewsmentioning
confidence: 99%
“…At the same time, attribute selectors should be agreed upon and matched to be similar feature determination. It means that when two or more techniques are demonstrated, the attribute names should be similar to other techniques even if one or two attributes are different from other techniques, as suggested in [35], [36], [37], [38], and [39]. Diabetic disease needs a unique study to improve the availability of investigation or reduce the variance and spread of this vital disease.…”
Section: F Features Selection Techniquesmentioning
confidence: 99%